2020
DOI: 10.17509/jpp.v20i1.24560
|View full text |Cite
|
Sign up to set email alerts
|

Praktik Guru dalam Pemanfaatan Teknologi di Kelas Bahasa Inggris

Abstract: Implementasi pemanfaatan teknologi yang efektif di yakini dapat meningkatkan motivasi siswa dalam belajar sekaligus membantu pekerjaan guru menjadi lebih mudah. Dalam praktik pemanfaatan teknologi di kelas, guru sebagai pemeran utama dalam proses belajar mengajar mempunyai peran yang unik dalam mengintegrasikan pelajaran bahasa Inggris dengan teknologi. Penelitian ini bertujuan untuk menginvestigasi sejauh mana teknologi di gunakan oleh guru dan faktor-faktor apa sajakah yang mempengaruhi praktik guru dalam pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Previous research has demonstrated that age and teaching experience impact the successful deployment of technology in the classroom (Indriani & Wirza, 2020). The similar conclusion may be drawn from research conducted by Raman and Yamat (2014), who showed that age and teaching experience posed obstacles for English teachers in adapting to technology implementation in the classroom.…”
Section: Age and Experiencesupporting
confidence: 64%
“…Previous research has demonstrated that age and teaching experience impact the successful deployment of technology in the classroom (Indriani & Wirza, 2020). The similar conclusion may be drawn from research conducted by Raman and Yamat (2014), who showed that age and teaching experience posed obstacles for English teachers in adapting to technology implementation in the classroom.…”
Section: Age and Experiencesupporting
confidence: 64%
“…It is in line with the study about ICT and advantages and benefits of ICT integration in education (Sabiri, 2020). Another researcher researched about implying the need for more intensive technology training to help teachers prepare more effective technology-integrated English learning (Indriani & Wirza, 2020). As a result, the researchers concentrate on the difficulties teachers confront while integrating ICT in EFL classrooms.…”
Section: Introductionsupporting
confidence: 59%
“…When it comes to integrating English lessons with technology in the classroom, the teacher, as the main actor in the teaching and learning process, plays a unique role. The most influencing factors for teacher practice in English classes are internal factors such as self-efficacy and teacher competence (Indriani & Wirza, 2020). Furthermore, a teacher's prior teaching experience has an impact on their perception of how to use technology.…”
Section: Artificial Intelligence Technology (Ai) Has Advanced At a Ra...mentioning
confidence: 99%
See 1 more Smart Citation
“…To encourage students to think critically, teachers need to ensure that the learning materials and content they use are appropriate for students to think critically. Indriani & Wirza (2020) add that the use of technology in learning is influenced by internal factors and external factors. One of the internal factors that influence learning is teaching experience.…”
Section: Encourage Critical Thinkingmentioning
confidence: 99%